Practical Soil-Shallow Foundation Model for Nonlinear Structural Analysis - Leblouba, M.; Al Toubat, S.; Rahman, Muhammad; Mugheida, O. (Hindawi Publishing Corporation, 2016)
© 2016 Moussa Leblouba et al.Soil-shallow foundation interaction models that are incorporated into most structural analysis programs generally lack accuracy and efficiency or neglect some aspects of foundation behavior. For instance, soil-shallow foundation systems have been observed to show both small and large loops under increasing amplitude load reversals. This paper presents a practical macroelement model for soil-shallow foundation system and its stability under simultaneous horizontal and vertical loads. The model comprises three spring elements: nonlinear horizontal, nonlinear rotational, and linear vertical springs. The proposed macroelement model was verified using experimental test results from large-scale model foundations subjected to small and large cyclic loading cases.